2015
DOI: 10.1039/c4ib00281d
|View full text |Cite
|
Sign up to set email alerts
|

Organizational metrics of interchromatin speckle factor domains: integrative classifier for stem cell adhesion & lineage signaling

Abstract: Stem cell fates on biomaterials are influenced by the complex confluence of microenvironmental cues emanating from soluble growth factors, cell-to-cell contacts, and biomaterial properties. Cell-microenvironment interactions influence the cell fate by initiating a series of outside-in signaling events that traverse from the focal adhesions to the nucleus via the cytoskeleton and modulate the sub-nuclear protein organization and gene expression. Here, we report a novel imaging-based framework that highlights th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 63 publications
(119 reference statements)
1
19
0
Order By: Relevance
“…Structural proteins such as CTCF, NuMA and lamins organize chromatin (Abad et al, 2007; Dechat et al, 2008; Kim et al, 2015), and by doing so they might redistribute when the phenotype of cells changes. Proteins like NuMA and splicing factor speckle SC35 have been used with high-content analysis of nuclear morphometric descriptors to identify changes in differentiation stages, notably of stem cells, before standard markers are modified (Liu et al, 2010; Vega et al 2015; Vega et al, 2017. More simply, changes in nuclear morphology such as shape (circularity) and size (area) might be sufficient to indicate a drastic impact of the microenvironment on cell behavior.…”
Section: Tissue Architecture-cell Nucleus Relationship To Control mentioning
confidence: 99%
“…Structural proteins such as CTCF, NuMA and lamins organize chromatin (Abad et al, 2007; Dechat et al, 2008; Kim et al, 2015), and by doing so they might redistribute when the phenotype of cells changes. Proteins like NuMA and splicing factor speckle SC35 have been used with high-content analysis of nuclear morphometric descriptors to identify changes in differentiation stages, notably of stem cells, before standard markers are modified (Liu et al, 2010; Vega et al 2015; Vega et al, 2017. More simply, changes in nuclear morphology such as shape (circularity) and size (area) might be sufficient to indicate a drastic impact of the microenvironment on cell behavior.…”
Section: Tissue Architecture-cell Nucleus Relationship To Control mentioning
confidence: 99%
“…Recently incorporation of high content image analysis approaches to evaluate cell response to engineered biomaterial platforms is gaining momentum. The Moghe lab at Rutgers has advanced the application of high content image informatics (HCII) to deduce biomarker profiles at the single cell level indicative of emergent phenotypes on a variety of platforms (Treiser et al 2010; Liu et al 2009; Vega et al 2015; Treiser et al 2007; Liu et al 2010). This approach is based on acquiring high resolution images of cellular reporters and performing high content analysis to acquire features quantifying reporter organization, in tandem with machine learning approaches to model sub-cellular reporter organization.…”
Section: High Content Image Informatics For Timely Screening and Cellmentioning
confidence: 99%
“…Specifically, the organizational metrics of interchromatin speckle factor SC-35 were used to profile hMSC lineage commitment and adhesion signaling in response to soluble cues and on varied platforms including patterned surfaces, fibrous scaffolds and micropillars (Vega et al 2015). In this approach, texture features capturing minute high-order variations in the sub-nuclear spatial organization of SC-35 were computed and utilized with machine learning approaches to generate a predictive cell-state classification model.…”
Section: High Content Image Informatics For Timely Screening and Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, cells often need to be cultured at high densities to induce differentiation or co-cultured for tissue engineering approaches, and in such cases it becomes difficult to segment cells on the basis of cytoplasmic actin. To overcome these limitations, we developed more sensitive and robust high content image informatics approaches that seek to classify cell states based on various nuclear reporters [8, 9]. In a recent study, we screened several nuclear reporters and demonstrated that the two dimensional sub-nuclear organization of splicing factor SC-35 served as an integrative marker to profile early osteogenic cellular responses across a series of surface patterns, fibrous scaffolds, and micropillars [8].…”
Section: Introductionmentioning
confidence: 99%